The Narrative of New Order Development in the Relationship between Pancasila and the Legitimacy of Power - Muhdar; Muhammad Ilham Daffa; Razi Alif Al Faiz; Abdel-Dzhalil Niyazov; Yahya Muhamad (Mahkota Science Publishers, 2025)
Under the New Order, development did not merely promise material progress, but also produced a political truth that made Pancasila a moral and technocratic language. This study aims not only to uncover the past but also to re-examine the relationship between Pancasila and development from a critical perspective to prevent the state's basic ideology from being reduced to a narrow political instrument. This study uses a qualitative-interpretative approach with a historical design grounded in critical discourse analysis. The results show that the New Order's development narrative indicates that the legitimacy of power did not primarily arise from debates about truth, but rather from engineering that made obedience appear moral, infrastructure appear as evidence of goodness, and social conflict appear as administrative disturbances, so that the public was trained to judge the government based on the visibility of work and order, rather than justice and rights. When development is used as aesthetics, control easily becomes virtue, eviction becomes reorganisation, silencing becomes stabilisation, and criticism becomes a threat to unity. Therefore, a constructive re-actualisation of Pancasila must dare to reverse this logic by making it a language of accountability that invites criticism, restoring conflict as a legitimate part of deliberation, and forcing development to be measured by its impact on dignity and the distribution of justice, while acknowledging the limitations of archival evidence and demanding further research that places the experiences of affected citizens at the centre of moral-political verification.